Relationship Between Self-Concept, Self-Efficacy, and Subjective Well-Being of Native and Migrant Adolescents - Céspedes, Cristian; Rubio, Andrés; Viñas, Ferran; Cerrato, Sara Malo; Lara-Órdenes, Eliseo; Ríos, Javier (Frontiers in Psychology, 2021)
In the last decade, the migrant population in Chile has substantially increased, where the rates have not only increased in the adult population, but also among children and adolescents, creating a potential for social and cultural development in the educational system. The present work analyzes the relationship between self-concept, self-efficacy, and subjective well-being in native and migrant adolescents in Santiago de Chile. The sample consisted of 406 students, 56.65% women, with an age range that fluctuated between 12 and 16 years, with an average of 13.36 years (SD = 0.96). Student's t-tests were used to compare the average of the constructs evaluated between natives/migrants and boys/girls participants. Subsequently, two multivariate models of simple mediation were constructed, one for natives and another for migrants, which assumed subjective well-being as a dependent variable, academic self-concept as an independent variable and the general self-efficacy as a mediating variable. In both models, gender was considered as a control variable. Results show that migrant students present higher levels of academic self-concept and general self-efficacy than native students. There are no differences with regard to well-being. In the case of gender, differences are observed only for the case of general self-efficacy, where boys present higher levels. On the other hand, a partial mediation is observed for the model of native students and a total mediation for the model of migrant students. The study yielded interesting results regarding the differences in the evaluation of the constructs of self-concept, self-efficacy, and subjective well-being in both groups. Such data can be used as inputs for the development of public policies for adolescents.